Adsorption equilibrium and dynamics of fixed bed adsorption of CH4/N2in binderless beads of 5A zeolite - Silva, José A.C. (2015)
The sorption equilibrium of methane (CH4) and nitrogen (N2) in binderless beads of 5A zeolite is presented between 305 and 373 K and pressures up to 3 bar in a static electronic microbalance. The adsorbed amount of CH4 and N2 is around 1.6 and 1.02 mol/kgads, respectively, at 305 K and 3 bar. A comparison of these values with the ones in literature shows that the adsorption capacity of the 5A binderless beads is 20% higher than that of the 5A binder commercial materials. The CH4 and N2 adsorption isotherms were fitted with the simplest Langmuir model with a prediction of the maximum amount adsorbed for both compounds of 5.0 mol/kg. The heats of sorption are -16.6 and -15.1 kJ/mol for CH4 and N2, respectively. In the overall pressure and temperature range the isotherms of N2 seems practically linear. However, it was observed that the experimental data of N2 at low coverage (below 0.2 bar) deviates slightly from Type I isotherms. Thereafter, the binary sorption of CH4 and N2 has been investigated in a fixed bed adsorber at 313 and 343 K and total pressures up to 5 bar for 50(CH4)/50(N2) and 75(CH4)//25(N2) mixture ratios diluted in an inert helium stream. A mathematical model was formulated to compute the dynamic behavior of the fixed bed adsorber using the extended binary Langmuir model, showing close agreement with the measured binary breakthrough experiments in the partial pressure range of the components above 0.2 and below 3 bar. © 2015 American Chemical Society.